Preliminary exploration of the relationship between ginsenoside content and endogenous hormones of multi stem ginseng and soil properties based on correlation analysis - Chen, Yuqiu; Xu, Zhefeng; Qi, Weichen; Zhang, Tao; Chen, Changbao; Shang, Xiaoling (Frontiers in Plant Science, 2025)
AimsCompared with single stem ginseng (G1), there is a significant gap in the research on the morphology and quality formation of multi stem ginseng (MG).MethodsThis study measured the ginsenoside content in the roots, stems, and leaves of 3-year-old single stem ginseng, double stem ginseng (G2), and triple stem ginseng (G3), as well as the endogenous hormone content in the rhizomes. At the same time, the physicochemical properties and enzyme activity of the rhizosphere and non-rhizosphere soil were measured, and the differences and connections between each indicator were analyzed.ResultsResultsThe content of ginsenosides in the roots of MG was significantly higher than that in G1, with the total ginsenoside content in G2 and G3 being 1.30 and 1.24 times higher than that in G1. There was a significant difference in the content of salicylic acid and brassinolide between G1 and MG. Differential analysis showed that aluminum bound phosphorus, aggregates with a particle size of 2-3 mm, and praseodymium were characteristic abiotic factors that contributed to differences in soil properties, fluorescein diacetate, peroxidase and invertase were characteristic enzymes that differed in different soils. A regulatory network of "soil abiotic factor-ginsenosides-soil enzymes" was constructed based on the results of correlation analysis.ConclusionsConclusionsThe interaction between soil enzymes (fluorescein diacetate, peroxidase, ascorbate peroxidase) and abiotic factors (praseodymium, neodymium, yttrium) were the main influencing factors of ginsenoside accumulation in MG. The results had improved our understanding and helped to better guide the planting of MG.